Insecticidal activity of essential oils against Rhyzopertha dominica - Kumar, Ranjeet (Indian Journal of Plant Protection, 2020)
The laboratory experiment was conducted to identify the chemical composition of Murraya koenigii, Citrus reticulata, Curcuma longa and Callistemon citrinus to determine the actual times required by essential oils to kill Rhyzopertha dominica. The chemical constituents of essential oil from leaves of M. koenigii identified by gas chromatography and gas chromatography mass spectrometry, were Î± pinene (26.82%), Î² pinene (13.41%) and sabinene (10.35%) as major compounds followed by limonene (10.31%) and longifolene (9.05%). The essential oil from peels of C. reticulata contained limonene (69.32%) followed by linalool (7.83%) as major constituents. The essential oil of C. longa was rich in camphene (25.56%) and Î± pinene (18.59%) followed by Î± humulene (11.78%), camphur (9.98%). In the leaves of C. citrinus, 1, 8-cineol (42.03%) and limonene (11.23%) were major constituents followed by Î± pinene (8.24%), and Î± terpineol (8.14%). The oil of M. koenigii + C. citrinus at 0.1% each, showed 56.7, 73.3, 93.3 and 100% mortality of R. dominica at 6, 12, 18 and 24 h after treatment, respectively. The oil of C. reticulata and C. citrinus caused 30.0 and 23.3% mortality, respectively, at 6 h after treatment, which increased to 100% in 24 h after treatment and the essential oil of C. longa was found least effective against the test insect.